Nervous coccidiosis in a calf - Değirmençay, Ş; Çomaklı, S; Özdemir, S; Hanedan, B (Journal of the Hellenic Veterinary Medical Society, 2023)
In this case report, a 9-month Swiss brown calf has been reported with neurological symptoms including seizures, opisthotonus, hyperesthesia, nystagmus, convulsions of the head and extremity muscles, watery brown faeces and mild blood in faeces. Eimeria spp. oocyst was found in the parasitological examination of the faeces, and it was suspected of nervous coccidiosis. When the brain tissue was examined, the numerous different forms of Eimeria spp were histopathologically detected in the brain parenchyma and brain capillaries. Eimeria spp which were found in the brain and large intestinal tissues were confirmed as Eimeria zuernii using specific primers with qRT-PCR. This case report emphasizes that Eimeria zuernii is located in the brain tissue of cattle for the first time in the world. We suspect that these agents may travel to the brain through the enteric blood vessels, and all the neurological symptoms detected in this calf may be due to the presence of these agents in the brain tissue. Therefore, this could be crucial knowledge on the pathogenesis of nervous coccidiosis.